Soluble biomarkers associated with chronic lung disease in older children and adolescents with perinatal HIV infection. (1st September 2021) - Hameiri-Bowen, Dan; Sovershaeva, Evgeniya; Flaegstad, Trond; Gutteberg, Tore Jarl; Ngwira, Lucky Gift; Simms, Victoria; Rehman, Andrea M.; Mchugh, Grace; Bandason, Tsitsi; Ferrand, Rashida Abbas; Rowland-Jones, Sarah; Yindom, Louis-Marie
Abstract : Objective: HIV-associated chronic lung disease (HCLD) is a common comorbidity in children and adolescents in sub-Saharan Africa (SSA). The pathogenesis of HCLD is unclear and may be driven by underlying dysregulated systemic immune activation and inflammation. We investigated the association between 26 plasma soluble biomarkers and HCLD. Design: Case–control analysis of baseline biomarker data from 336 children and adolescents (6–19 years old) with perinatal HIV infection (PHIV) and HCLD (cases) and 74 age-matched and sex-matched controls with PHIV but no CLD. HCLD was defined as having a forced expiratory volume in one second (FEV1) z score less than −1 with no reversibility. Methods: Cryopreserved plasma collected at recruitment was used in a multiplex bead assay (Luminex) to measure baseline levels of soluble biomarkers. Logistic regression alongside data-reduction and techniques quantifying the interconnectedness of biomarkers were used to identify biomarkers associated with odds of HCLD. Results: Biomarkers of general immune activation and inflammation (β2M, CRP, sCCL5, GCSF, IFN-γ, IP-10), T-cell activation (sCD25, sCD27), platelet activation (sCD40-L), monocyte activation (sCD14), coagulation (D-Dimer), cellular adhesion (E-selectin), and extracellular matrix degradation (MMP-1, MMP-7, MMP-10) were associated with increased odds of HCLD. Exploratory PCA and assessment of biomarker interconnectedness identified T-cell and platelet activation as centrally important to this association. Conclusion: HCLD was associated with a large number of soluble biomarkers representing a range of different pathways. Our findings suggest a prominent role for T-cell and platelet activation in HCLD. Abstract : Supplemental Digital Content is available in the text